Rancang Sistem GPS Tracker Pada Motor Berbasis Arduino - Wijaya; Asni Tafrikhatin; Ajeng Tiara Wulandari; Fauzi, Muflihun (Politeknik Piksi Ganesha Indonesia, 2021)
Motorcycle is a means of transportation that is widely used in Indonesia because it is very efficient in its use. However, motorcycle crimes do not happen very often. Therefore, in this final project, a motor vehicle system with an Arduino-based GPS Tracker is designed. The aim is to detect the presence of the motorcycle through the GPS system and to determine the accuracy of the position indicated by the GPS Tracker. The design method uses Arduino Uno, GSM module, GPS module, Smartphone and sim card. In the initial conditions, the activated gps system is activated first, the GPS will send the coordinates to the Arduino. Then it will be sent via cellular network via SMS to a number that is already connected to the system, then the position of the motorcycle will be monitored using GPS.The final design results show that the position of motorized vehicles can be monitored via a smartphone using a GSM network. The results of testing the time of sending short messages that are delayed are for 9 to 12 seconds.